2004
DOI: 10.1101/lm.81404
|View full text |Cite
|
Sign up to set email alerts
|

Extinction Training Regulates Neuroadaptive Responses to Withdrawal from Chronic Cocaine Self-Administration

Abstract: Cocaine produces multiple neuroadaptations with chronic repeated use. Many of these neuroadaptations can be reversed or normalized by extinction training during withdrawal from chronic cocaine self-administration in rats. This article reviews our past and present studies on extinction-induced modulation of the neuroadaptive response to chronic cocaine in the mesolimbic dopamine system, and the role of this modulation in addictive behavior in rats. Extinction training normalizes tyrosine hydroxylase levels in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 101 publications
5
97
4
Order By: Relevance
“…Role of Narp in morphine-induced behaviors HS Crombag et al decrease in Narp expression in the NAc shell and this decrease is reversed by extinction training (Self et al, 2004). Although these biochemical results were obtained in studies conducted on rats undergoing cocaine self-administration and our studies employed passive administration of morphine to mice, taken together these results suggest that Narp may be important in the alterations in GluR subunit expression observed in the NAc following drug withdrawal and extinction.…”
Section: Discussioncontrasting
confidence: 50%
“…Role of Narp in morphine-induced behaviors HS Crombag et al decrease in Narp expression in the NAc shell and this decrease is reversed by extinction training (Self et al, 2004). Although these biochemical results were obtained in studies conducted on rats undergoing cocaine self-administration and our studies employed passive administration of morphine to mice, taken together these results suggest that Narp may be important in the alterations in GluR subunit expression observed in the NAc following drug withdrawal and extinction.…”
Section: Discussioncontrasting
confidence: 50%
“…These studies have demonstrated that an extinction training experience can restore tyrosine hydroxylase to predrug levels in the nucleus accumbens shell, whereas an equivalent abstinent period showed a persistent deficit in tyrosine hydroxylase protein levels [23]. Similarly, a down regulation of NMDA receptor NR1 subunit during abstinence is reversed by extinction [25]. Finally, an extinction induced upregulation of GluR1 AMPA receptors occurs in the nucleus accumbens shell [32], and an upregulation of tyrosine hydroxylase also has been observed in the ventral tegmental area following extinction training [23].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved with the resulting effects of extinction training as they may relate to the self-administration of addictive substances have been investigated at the molecular level in the ventral tegmental area and nucleus accumbens regions of the brain [25]. These studies have demonstrated that an extinction training experience can restore tyrosine hydroxylase to predrug levels in the nucleus accumbens shell, whereas an equivalent abstinent period showed a persistent deficit in tyrosine hydroxylase protein levels [23].…”
Section: Discussionmentioning
confidence: 99%
“…Extinction therapies could also be of benefit in the treatment of addiction. Although there have been studies investigating extinction of cue-induce craving responses in humans (Childress et al 1993;Carter and Tiffany 1999), there have been relatively few clinical or preclinical studies investigating pharmacological manipulations of extinction of human drug seeking and addiction-related behaviors in animal models (Self et al 2004).…”
mentioning
confidence: 99%